Spatial distribution and interaction of four species of the catfish genus Hypostomus Lacépède with bottom of Rio São Francisco, Canindé do São Francisco, Sergipe, Brazil (Pisces, Loricariidae, Hypostominae) - J. C. Garavello; J. P. Garavello (Brazilian Journal of Biology)
The large catfishes, genus Hypostomus Lacépède, are common species in almost all freshwater environments of South America. The behavior of specimens from the species Hypostomus alatus, Hypostomus francisci, Hypostomus cf. wuchereri, and Hypostomus sp., from the region downstream from the Xingó Hydroelectric Power Dam, located in Canindé do São Francisco on the Rio São Francisco, were observed. Morphological characters collected from preserved specimens were also studied in the laboratory, in order to shed light on interactions between those fishes and the river bottom. In addition, the formulation of Gatz (1979) was applied to better explain the environmental interactions of Hypostomus species. This study revealed that the fishes utilize their suckers, through a mouth equipped with an oral disk, as well as the pectoral, pelvic, and caudal fins areas, to interact with the rocky river-bottom. The comb-toothed inferior mouth of the Hypostomus showed itself able to grasp green algae on the river bottom. With the help of the oral disk and sucker mouth, which anchor the fishes, in conjunction with the arched design of pectoral and pelvic fin spines, they are also able to remain upright while exploring this substratum. In addition, their large, concave caudal-fin is associated with fast locomotion over short distances. This combination of characteristics allow these fish to live on the bottom of large South American rivers.